Evaluating energy optimization through BIM simulation analysis for office buildings in Malaysia / Mohamad Shahin Shahdan ... [et al.] - Shahdan, Mohamad Shahin; Zainal Abidin, Mohammad Nazrin; Ahmad Fuad, Farah Hanna; Hassan Naziri, Ahmad Faiz (2021)
Energy efficiency can be described simply as using less energy to do the same job, which is to minimize energy waste. Buildings are expected by most nations to attain an energy-efficient rating, which may be done effectively via monitoring thermal load. Nowadays, with the advanced technology and new software, there are many tools that can be used by the designer to help them in achieving the energy efficient building status. Therefore, by using Building Information Modelling (BIM) software, energy optimization can be explored and analyzed effortlessly at the early design stage. However, this software is not being used by all building professionals in a project since not all consultants own this software, thus hindering the coordination among them. Consequently, the exploration of BIM software is limited and sometimes overlooked and left too late at the end of the design process thus eliminating its maximum potential. Hence, this paper aims to study the capability and competency of BIM simulation tools software through Autodesk Revit in helping the designers to evaluate and analyze energy optimization in a building; therefore, helping with the design decision making. As for simulation, office building has been chosen to be evaluated concerning the energy optimization on thermal load by manipulating various materials thermal transmittance. Based on the analysis report, it is easy to determine the best measure for energy optimization regarding the thermal load value. In conclusion, along with the designer skills and knowledge, energy simulation tools of the selected BIM software does have the capabilities to help designers explore various methods at the early stage before the commencement of any building. Lastly, we would like to suggest any future studies related to this topic to experiment with different simulation tools or software.